PEMBELAJARAN MENULIS TEKS EKSPOSISI DENGAN MENGGUNAKAN MODEL MIND MAPPING PADA SISWA KELAS VIII DI SMP - Mira Miranda (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Writing is a skill to put ideas and ideas into writing. Writing skills are not easy to do in learning, because many students cannot put their ideas and ideas into writing. Exposition text is a text that needs to express ideas and ideas when writing it. Therefore, this research was conducted on the background of how the learning process and the results of students' exposition text writing skills improved. The purpose of this study was to determine students' exposition text writing skills using a mind mapping model. The research method used in this research is descriptive qualitative. The subjects of this study were 32 students of class VIII A at SMPN 2 Cihampelas. The results showed that 18 students got a high score, 8 students got a sufficient score, and 6 students got a low score. The results of the study concluded that using a mind mapping model in class VIII A students could improve students' skills in writing exposition text.